Diversidade de Nitidulidae e Curculionidae (Coleoptera, Insecta) em cambarazais e cordilheiras do Pantanal de Poconé, Mato Grosso, Brasil - Oliveira, Maria Eduarda Basso de (2024)
This study evaluated the influence of the seasonality and complexity of habitats in the Pantanal on the Nitidulidae and Curculionidae families associated with the canopies of cambarazal and cordilheira in the Pantanal of Poconé, MT. Collections occurred during the dry (2012) and flood (2013) periods using canopy fogging. A total of 24,973 Coleoptera individuals were collected and grouped into 52 families, of which Nitidulidae (7,030 ind.) and Curculionidae (4,442 ind.) were the most abundant. In the cordilheira, 48 plant species (137 ind.) were sampled and in the cambarazal, 15 species (108 ind.) were sampled, with 56.5% corresponding to Vochysia divergens, the predominant species. Nitidulidae were identified in 3 subfamilies, 7 genera and 20 morphospecies, while Curculionidae were identified in 13 subfamilies, 59 genera and 242 morphospecies. The composition of Coleoptera communities in the canopy, especially Nitidulidae and Curculionidae, is influenced by seasonality and the phytophysiognomies of this biome. The abundance of Coleoptera did not significantly differ between the two phytophysiognomies or between the two sesaons. Although Curculionidae were less abundant in the cordilheira (986 ind.) than in the cambarazal (3,455 ind.), it was confirmed that the canopy supported the highest richness and diversity of these taxa. The richness and diversity of Curculionidae in the cordilheira did not change, while cambarazal had greater diversity in the dry season. There are few Curculionidae that feed on wood and fungi (888 individuals), and the majority consume leaves, flowers, fruits and seeds (3,554 individuals). The presence of these resources in the phytophysiognomy canopy is essential for the life cycle of the individuals. Nitidulidae was more abundant in the cordilheira (4,027 ind.) than in the cambarazal (3,003 ind.). Diversity analysis, revealed that flooding was the period with the greatest diversity of Nitidulidae, both in the cambarazal and in the cordilheira, with the dry period being the least diverse, in both phytophysiognomies. The richness of Nitidulidae changed only in the cordilheira, being greater during the flood. Three trophic guilds of Nitidulidae were identified in the cordilheira (anthophiles, fungivores and saprophages), and two were identified in the cambarazal (anthophiles and saprophages). Among the 20 morphospecies sampled, Mystrops species 2 was the most abundant (6,759 individuals; 96.6%), directly influencing the distribution of trophic guilds in the canopy. The guilds changed between the phytophysiognomies and the seasons evaluated, reflecting the availability of different food resources in the canopy in each seasonal period and phytophysiognomies in the Pantanal. Data analyses indicate that the flood pulse, phytophysiognomy and phenology of plant species influence the distribution of the Coleoptera, Nitidulidae, and Curculionidae communities in different ways and influence the richness, diversity, and distribution of the Nitidulidae and Curculionidae trophic guilds in the canopy of the cambarazal and cordilheira of the Poconé Pantanal, MT.